Malawi : Request for an Extension of the Extended Credit Facility Arrangement-Press Release and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the Malawi authorities, request for a short extension (June 30, 2016) to their arrangement under the Extended Credit Facility (ECF) that is currently due to expire on May 22, 2016. The extension is needed to provide time for the authorities to implement two prior actions for completing the seventh and eighth reviews. These comprise the reconciliation of government bank accounts for the first half of FY2015/16 and another on preparing a report on the flow and stock of domestic arrears at end-2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet